Development of e-module STEAM-Integrated problem based learning for salt hydrolysis topic - Lusi Marvita Sari; Andromeda Andromeda (Jurnal Pijar Mipa, 2023)
Teaching materials as a support in the learning process in this technological era can be in the form of e-modules. Using e-modules in the learning process is declared effective, with a marked increase in student learning outcomes. This research aims to produce an integrated STEAM Problem-Based Learning E-Module of Salt Hydrolysis and determine its validity and practicality level. The type of research used is research development or Research and Development (R&D). The development model used is the Plomp model, which consists of 3 stages, namely: (1) Preliminary Research, (2) the Development or Prototyping Phase, and (3) Trial and Assessment (assessment phase). This research is limited to the development stage, namely the validity and practicality test. The research instrument used was a validity and practicality questionnaire. Five validators validated the e-module, while the practicality test was carried out by three chemistry teachers and 12 students in class XII MIPA senior high school SMAN 15 Padang. The results of the validation analysis obtained an average content validity test value of 0.87 with a valid category and an average media validity test value of 0.90 with a valid category. At the same time, the practicality tests of teachers and students obtained 91% and 91%, respectively, in the very practical practicality category. In conclusion, the salt hydrolysis e-module based on STEAM integrated Problem-Based Learning for class XI SMA/MA, which has been developed, is valid and practical.